(untitled) (Global Journal of Management and Business Research, 2014)
The financial crisis strongly marked states around the world due to the increasing indebtedness of the states and of the banks, which went through, with few exceptions, a prolonged recession. The year 2014 seems to mark a new economic cycle, and the turnaround is seen in Romania, a state which has made progress in reinforcing and stabilizing the public finance sector, as well as resuming economic growth which must be followed by economic development. The concept of economic development is more complex than economic growth, which involves the design of certain directions for long-term sustainable growth, based on the optimum use of available resources, on the continuous development of innovative potential and human capital, reducing social inequalities, etc., where the investment process has a particularly important role..